(untitled) (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2025)
The Internet of Things (IOT) aims to transform our surroundings—including our houses and flats, places of employment, and cars—into something smarter, more measurable, and more hospitable. Voice technology can make it easier to play music, create countdowns, or receive information. It is easier to monitor actions both inside and outside, as well as to recognize and engage with visitors, thanks to surveillance cameras. Intellectual light bulbs could perhaps give the illusion as if we are parents’ house even when we are not, but instead smart devices can help us warm heat our homes before we arrive. When we look outside the house, sensor nodes can tell us how noisy, frustrating, or contaminated our enviroment But several of these developments could have a big impact on our right to privacy. Users are likely to interact with internet-enabled gadgets for the first time through home automation, another market where the main tech companies are engaged in strong competition. Examples include smart sensors, smart lighting fixtures, camcorders, smart thermostats, and the smart fridges. The issues related to the Internet of Things, health, and privacy are discussed in this paper, along with suggestions for IoT solutions.